Female Breadwinners, Money and Shame: How Financial Planners Can Help - Heath Carelock; Darren Hinds; Sabina Lewis; David Hoffman; Meghaan Lurtz (Journal of Financial Therapy, 2022)
Women who earn more than their male spouses, in a heterosexual relationship, are a growing underrepresented group. Some female breadwinners feel shame related to the reversal of traditional gender roles. These feelings of shame can interfere with the financial planning process. Five interventions are provided as examples of how financial planners, financial therapists, or financial counselors and other financial professionals can help female breadwinners with shame issues. Whether a planner uses one of these interventions, some other intervention, or no intervention at all will depend on their training and level of competence. Using an intervention can help a female breadwinner deal with shame and progress in the financial planning process.
Keywords: Female Breadwinners; Shame; Money; Financial Planning